CTIM-01. PHASE II TRIAL OF PEMBROLIZUMAB AND LENVATINIB FOR LEPTOMENINGEAL METASTASES. (12th November 2021) - Wang, Nancy; Gerstner, Elizabeth; Cahill, Daniel; Oh, Kevin; Cahill, Jennifer; Brastianos, Priscilla
Abstract: Leptomeningeal metastasis (LMD) is a late complication of cancer with poor prognosis and median survival of approximately 4-6 weeks without treatment. Whole brain radiation remains the mainstay of treatment, however it can cause significant neurocognitive sequelae and has not been shown to prolong overall survival. Thus, new treatment strategies are urgently needed to improve outcomes in patients with LMD. Results from recent Phase 2 studies of immune checkpoint inhibitors in LMD shows promising improvement in overall survival. Combining anti-VEGF therapy and immunotherapy may control symptoms due to inflammation and tumor-induced irritation, minimize steroid use, and promote improved efficacy of immunotherapy through modulation of the tumor immune microenvironment. We designed a multi-institutional, single-arm Phase 2 study of pembrolizumab in combination with lenvatinib in patients with LMD from any solid tumor. The primary objective is to estimate the overall survival rate at 6 months (OS6). A Simon two-stage design with a total sample size of 19 evaluable patients will be used to compare a null hypothesis of OS6 of 25% against an alternative hypothesis of 55%. Secondary objectives include assessing safety of pembrolizumab and lenvatinib in this patient population, systemic response rate, intracranial/intraspinal response rate, and progression-free survival. We will also explore clinician-reported neurologic outcomes and patient-reported quality of life and symptom burden. Blood, cerebrospinal fluid, and tissue biomarkers will be analyzed to determine predictors of response. Patients must be on minimal doses of steroids prior to study enrollment and cannot have received prior immune checkpoint inhibitor or anti-VEGF therapy. Response to treatment will be determined using RANO-BM for intracranial disease and RECIST 1.1 for systemic disease. Study accrual is anticipated over 12-24 months with anticipated total study duration of 30 months.